Prevalence of cervical alterations in patients with temporomandibular dysfunction in a specialized referral service (Research, Society and Development, 2022)
The muscular structures of the body are interconnected, with the cervical and masticatory systems forming a part of the complex called Manducatory System, which is a part of the organic postural system. Alterations in one of these components induce compensatory changes and affect other systems. These adjustments can lead to temporomandibular dysfunction (TMD) and craniocervical dysfunction. Their etiology is multifactorial, with a high prevalence of chronic pain, especially in cases of headaches. Cervical alterations are common in TMD, considering the degree of pain and discomfort experienced by patients. This study aimed to conduct a survey of medical records regarding the frequency of TMD with cervical changes in patients who visited our institution between 2017 and 2019. Approximately 81.86% of patients showed cervical changes, and the sternocleidomastoid muscle showed the greatest involvement, especially in the mastoid portion. TMD showed greater involvement in women and was most prevalent between 40-49 years of age. This study contributes to scientific literature, since there are few reports highlighting the need to promote research and financial support in this subject area, which can help improve the diagnosis and treatment of these craniocervicomandibular disorders.